Nematicidal Activity of the Essential Oil of Three Varieties of Tagetes minuta from Argentina - Massuh, Yamile (2017)
Essential oils composition of three Tagetes minuta varieties and a wild population (WP) from Argentina and their nematicidal activity against root-knot nematode, Meloidogyne javanica, in vitro and in vivo are described. All T. minuta EOs tested were very active against nematode juveniles (J2), by the strongest nematicidal effects were exhibited by the TmV3 variety oil, characterized by a high content of (E)-ocimenone. High nematode egg hatching suppression (> 90%) was induced by TmV3 EO after five days of incubation. In vivo tests on tomato seedlings showed a significant reduction of infection rate of M. javanica J2 treated with TmV3 and WP oils at sub lethal dose. Therefore, EOs from stables new varieties of T. minuta could be environmentally friendly nematicidal agents.